Alu transcripts: cytoplasmic localisation and regulation by DNA methylation. - Liu, W M (1994)
Full length Alu transcripts in HeLa cells are detected by primer extension using reverse transcriptase and are also analyzed as cloned cDNA sequences. The 5' end of these transcripts corresponds to the transcriptional start site for RNA polymerase III indicating that these RNAs are transcribed from their internal polymerase III promoters. The Alu transcripts found in cytoplasmic poly A+ RNAs appear to be organized into RNPs as assayed by sucrose gradient sedimentation. Present at about one hundred to one thousand copies per cell, the Alu transcripts are rare as compared to 7SL RNA. In agreement with previous reports that methylation inhibits Pol III-directed transcription of Alu in vitro, treatment of HeLa cells with 5-azacytidine results in Alu DNA hypomethylation and an increase in the abundance of the Alu transcript. Sequence analysis shows that many different Alu repeats including members of all subfamilies are transcribed by Pol III in vivo. cDNA sequences of the Pol III-directed transcripts exactly match the A box of the Pol III promoter element whereas in other Alu transcripts this element is not faithfully conserved.